Improved agro-management in rice (Oryza sativa) and chickpea (Cicer arietinum) at rainfed lowland ecology - Ghosh, A; Singh, R K; Singh, O N (The Indian Journal of Agricultural Sciences, 2020)
An on-farm study was conducted in Odisha during 2014-2016 growing kharif rice (Oryza sativa L.) and chickpea (Cicer arietinum L.) at rainfed lowland ecology. Impacts of improved tillage and nutrient management was studied along with supplementary irrigation in chickpea. Rice producing comparable grain yields (3.45-3.72 t/ha) at minimum and conventional tillage (3.50-3.75 t/ha) was significantly higher than that (2.52-2.65 t/ha) at zero tillage. Chickpea produced comparable seed yields at zero (14.4-14.9 q/ha), minimum (14.4-14.8 q/ha) or conventional tillage (14.5- 14.8 q/ha) also. Rice with state recommended dose of fertilizers (SRDF) or INM produced comparable grain yields (3.10-3.20 t/ha and 3.08-319 t/ha). Chickpea also with SRDF or INM produced comparable seed yields (15.20-15.50 q/ha and 15.00-15.40 q/ha). Irrigation in chickpea either at pod development stage alone or also at pre-flowering stage enhanced seed yields (15.50-16.20 q/ha and 14.80-15.60 q/ha respectively), significantly higher than that (8.80-9.20 t/ha) at residual soil moisture situations. Thus, the study ensured maximum profitability of around ` ₹ 100000.0/ha while growing rice with improved nutrient management at conventional or minimum tillage followed by chickpea at conventional, minimum or zero tillage management. Therefore, the study could suggest the prospect of system based improved rainfed lowland rice fallow management in a rice-chickpea cropping system.